The Complexities of SDGs Goal 5 and 13 in ASEAN Region: A Comparative Study between Balinese and Cambodian Women Campaign on Climate Action - Paramitha, Gracia; Denni Rajagukguk; Revy Marlina (Technium Social Sciences Journal, 2024)
Women tend to be objects and victims of climate change impact. The International Union for Conservation of Nature (IUCN) 2020 found that gender-based violence was aligned with climate and environmental crises in various developing countries. In addition, 9.9 women were affected heavily by natural disasters in Indonesia (BPS, 2017). Meanwhile, only 20% of women’s leadership constitutes the entire energy sector (WEF, 2022). Another important statement from the IPCC (2022) said that women (particularly pregnant women) became highly impacted by the climate crisis. The Assessment Report on the State of Gender Equality and Climate Change in ASEAN (2022) built evidence on the importance of recognising women’s roles in climate action in ASEAN countries. In light of this background, this paper will analyse the critical complexities of ASEAN women’s leadership towards climate action in order to evaluating the implementation of SDGs goal 5 and 13. To have further deep analysis, this paper will explore the case study of Balinese and Cambodian women who have best practices of climate action, locally, nationally and globally, which also enhance ASEAN countries’ commitment to SDGs. Some of the best practices in Cambodia include a Renewable Energy (RE) programme that actively engages with and promotes women-led energy enterprises by implementing “The Smoke-Free Village” approach and training women as champions for gender-transformative Disaster Risk Reduction (DRR). Meanwhile, in Bali, Balinese women play an important role in climate action by establishing the Bali Women Climate Entrepreneur Project which encourages 10 start-ups to join the program and many other best practices to be explored further. As a methodology, the best practices of women leadership in both countries will be collected through literature reviews, interviews, statistics from the Balinese and Cambodia government/SDGs centres, and other relevant documents’ review. From those sources, this paper is expected to be the guide to mapping women leadership in climate action and also become a guide on how to develop effective communication for women in the ASEAN region on climate change.